Representing Personal Experiences in EFL Students' Narrative Writing: Language Choice and Plot Structural Patterns - Junaid, Junaid; Asnidar , Anin (FOSTER: Journal of English Language Teaching, 2026)
This study aims to examine patterns of personal experience representation in undergraduate students’ narrative writing, focusing on (1) language choice, including diction, register, and personalization, and (2) story plot structure, encompassing chronological plots, flashbacks, and narrative turning points. The study employs a descriptive quantitative design using quantitative content analysis of students’ narrative texts. Each text was analyzed using a structured coding scheme that classified linguistic features. The study has several limitations, including a relatively small sample size and a context limited to a single institution. The sample consisted of 30 undergraduate students from the English Language Education program at Muhammadiyah University of Makassar (N = 30). Data were drawn from one study program and one institution only, and the analysis focused on narrative text products without in-depth exploration of students’ cognitive writing processes, which limits the generalizability of the findings. Data were collected through quantitative content analysis of 30 narrative writing tasks, supplemented by a short reflective questionnaire. The results reveal two dominant patterns. First, the use of highly interpersonal language, characterized by frequent first-person pronouns and emotional expressions, is positively correlated with retrospective plots or flashbacks. Second, the use of formal–descriptive language tends to be associated with linear chronological plots. The novelty of this research lies in its systematic and measurable identification of the relationship between language choice and plot structure as patterns of students’ personal experience representation, rather than treating linguistic features or narrative structures as isolated characteristics, as commonly found in previous studies. Practically, these findings imply the need for narrative writing instruction in higher education that explicitly links language choice with plot development through reflective writing tasks, practice with varied narrative structures, and rubric-based feedback to enhance the quality, coherence, and depth of students’ narratives.